2020
DOI: 10.1177/0003134820964491
|View full text |Cite
|
Sign up to set email alerts
|

Rewarding On Time Start Times in Operating Rooms Improves Efficiency

Abstract: Background The average cost of running an operating room (OR) is approximately $37.00 a minute. Therefore, every effort should be made to start in a timely manner. There are several factors at play that can cause OR delays. Attaining consistent start times is a multidisciplinary task, which requires good communication and rewards for efficiency. Methods At our institution, a “star system” was implemented to improve compliance with timely start times. All OR staff (scrub tech, OR nurse, anesthesiologist, and ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 9 publications
0
4
0
1
Order By: Relevance
“…È risultato esserci una differenza significativa nei tre mesi precedenti e successivi all'implementazione del progetto, con i ritardi scesi dal 71% al 54%. Ne è risul-tato che l'efficienza migliora se il personale è motivato e premiato, infatti gli incentivi sono risultati essere un ottimo metodo per incoraggiare tutto il personale di sala operatoria a iniziare in tempo gli interventi [19] . Lo studio retrospettivo ha limitato la disponibilità dei dati e la possibilità di ottenere informazioni dettagliate, inoltre l'assenza del processo di randomizzazione rende reale il problema del selection bias.…”
Section: Discussioneunclassified
“…È risultato esserci una differenza significativa nei tre mesi precedenti e successivi all'implementazione del progetto, con i ritardi scesi dal 71% al 54%. Ne è risul-tato che l'efficienza migliora se il personale è motivato e premiato, infatti gli incentivi sono risultati essere un ottimo metodo per incoraggiare tutto il personale di sala operatoria a iniziare in tempo gli interventi [19] . Lo studio retrospettivo ha limitato la disponibilità dei dati e la possibilità di ottenere informazioni dettagliate, inoltre l'assenza del processo di randomizzazione rende reale il problema del selection bias.…”
Section: Discussioneunclassified
“…This intervention improved ontime starts from 54% in the preintervention period to 71% postintervention. 31 Instituting a systems-based approach and adding protocols have also been shown to be effective in decreasing delays to the first case starts. Han et al 32 were able to decrease delays in first case starts simply by implementing protocols that stated that surgical residents must mark and consent the first patients of the day at least 30 minutes before the scheduled start time.…”
Section: First Case Startsmentioning
confidence: 99%
“…Similarly, Jreije and colleagues rewarded OR team members (scrub technician, OR nurse, anesthesiologist, and surgeon) with a gift card after achieving 10 on-time starts. This intervention improved on-time starts from 54% in the preintervention period to 71% postintervention 31…”
Section: First Case Startsmentioning
confidence: 99%
“…The authors showed a significant increase in the number of first cases that started on time, and they noted a higher level of enthusiasm at the beginning of each clinical day. 1 However, we believe that the current study can be improved upon immediately from an operational and financial perspective.…”
mentioning
confidence: 92%
“…Perhaps the waning enthusiasm for the current project could be directed into a different initiative, one that encouraged the interests of the seeming non-adopter. Richard M. Dobson, DO 1 , and Mitchell H. Tsai, MD, MMM, FASA, FAACD 2…”
mentioning
confidence: 99%